2012
DOI: 10.4315/0362-028x.jfp-11-181
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Foreign Bodies in Foods Using Continuous Wave Terahertz Imaging

Abstract: Foreign bodies (FBs) in food are health hazards and quality issues for many food manufacturers and enforcement authorities. In this study, continuous wave (CW) terahertz (THz) imaging at 0.2 THz with an output power of 10 mW was compared with X-ray imaging as techniques for inspection of food for FBs. High-density FBs, i.e., aluminum and granite pieces of various sizes, were embedded in a powdered instant noodle product and detected using THz and X-ray imaging. All aluminum and granite pieces (regular hexahed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…THz spectroscopy is ideally suited for the identification of biological or complex inorganic molecules [1], the study of collective excitations in condensed media [2][3][4], for plasma diagnostics [5]. Applications of THz radiation range from medicine [6], food industry process control [7], to security concerns [8], telecommunication [9], etc. Impressive progress has been achieved in the last few years in the development of intense THz sources.…”
mentioning
confidence: 99%
“…THz spectroscopy is ideally suited for the identification of biological or complex inorganic molecules [1], the study of collective excitations in condensed media [2][3][4], for plasma diagnostics [5]. Applications of THz radiation range from medicine [6], food industry process control [7], to security concerns [8], telecommunication [9], etc. Impressive progress has been achieved in the last few years in the development of intense THz sources.…”
mentioning
confidence: 99%
“…Moreover, according to the previous reports on food quality monitoring by continuous-wave (CW) sub-THz imaging, it has been shown that even low-density organic materials can be well discriminated at these frequencies [4,[11][12][13]. This implies that the sub-THz imaging technique displays distinctive advantages for food quality inspection compared to conventional X-ray imaging systems.…”
Section: Introductionmentioning
confidence: 96%
“…Even though the X-ray systems are useful for discriminating both metallic and nonmetallic materials in food products, the identification of low-density objects (often organic materials such as insects and plastics) is known to be challenging [2]. Thus, complications caused by the presence of those flaws in food products are still being reported, and this represents a significant concern for many food manufacturers and food retailers [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, X-ray inspection equipment has been used often in the food industry 18 due to its highthroughput (detecting and sorting) and good penetration capabilities, compared with alternative technologies such as terahertz and sub-terahertz imaging 19,20 . These useful technologies have expanded to the pharmaceutical industry, where companies have demonstrated their use for inspecting drug packages to detect foreign matter and wrong or missing contents.…”
Section: Introductionmentioning
confidence: 99%